2007
DOI: 10.1002/joc.1545
|View full text |Cite
|
Sign up to set email alerts
|

Non‐linearity in statistical downscaling: does it bring an improvement for daily temperature in Europe?

Abstract: Several linear and non-linear statistical downscaling methods are compared for winter daily temperature at eight European stations. The linear methods include linear regression of gridpoint values (pointwise regression) and of predictors' principal components (PC regression). The non-linear methods are represented by artificial neural networks. The non-linearity is also achieved by a stratification of data by classification of circulation patterns and a linear regression conducted separately within each class.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Comparison studies show both methods could have superiority to others while dealing with different study areas, predictands, predictors, and statistical indicators used for judgement [48,49]. Thus, because there is no a priori supposition of the relationship, we would try both multi-linear and ANN models in our study for regression.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison studies show both methods could have superiority to others while dealing with different study areas, predictands, predictors, and statistical indicators used for judgement [48,49]. Thus, because there is no a priori supposition of the relationship, we would try both multi-linear and ANN models in our study for regression.…”
Section: Introductionmentioning
confidence: 99%
“…Among nonlinear methods is worth mentioning the use of different types of NN which are reported to outperform linear models (Weichert and Bürger, 1998;Miksovsky and Raidl, 2005;Davy et al, 2010). Other works suggest that for statistical downscaling of temperature, linear models cannot be beaten by NN (Huth et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…1; note that, hereafter, Zi stands for a specific zone. Over this region we considered a number of atmospheric variables (see Table 1) typically used as predictors in temperature downscaling studies (Benestad 2002;Huth 2002;Hanssen-Bauer et al 2005;Huth et al 2008). It has been recently shown that these variables -considering anomalies-are suitable predictors for climate change studies, since their distribution is skillfully reproduced by Global Climate Models (GCMs) in the area under study (see Brands et al 2011a).…”
Section: Geographical Zones and Datamentioning
confidence: 99%